Cryogenic characterization and modeling of a CMOS floating-gate device for quantum control hardware. (March 2022) - Castriotta, Michele; Prati, Enrico; Ferrari, Giorgio
Highlights: The operation at cryogenic temperature of a floating-gate CMOS device is demonstrated. Compact simulative models for tunneling and hot-electron injection are validated both at 300 K and 15 K. A fine tuning of the charge stored in the floating-gate device is shown at cryogenic temperature. Abstract: We perform the characterization and modeling of a floating-gate device realized with a commercial 350-nm CMOS technology at cryogenic temperature. The programmability of the device offers a solution in the realization of a precise and flexible cryogenic system for qubits control in large-scale quantum computers. The device stores onto a floating-gate node a non-volatile charge, which can be bidirectionally modified by Fowler-Nordheim tunneling and impact-ionized hot-electron injection. These two injection mechanisms are characterized and modelled in compact equations both at 300 K and 15 K. At cryogenic temperature, we show a fine-tuning of the stored charge compatible with the operation of a precise analog memory. Moreover, we developed accurate simulation models of the proposed floating-gate device that set the stage for designing a programmable analog circuit with better performances and accuracy at a few Kelvin. This work offers a solution in the design of configurable analog electronics to be employed for accurately read out the qubit state at deep-cryogenic temperature.